Optimization of low signature base bleed propellant formulations. (September 2019) - Youssef, Ehab M; Elshenawy, Tamer; Mostafa, Hosam E; Radwan, Mostafa; Elbeih, Ahmed
Abstract: Base bleed (BB) projectile is one of the choices to minimize projectile base drag leading to 30% range extension. The secondary smoke resulting from the burning of BB is considered to be one of the drawbacks of the BB and it is an essential factor in detecting the projectile flight towards the target. Based on intensive ICT formulations results, optimization study has been carried out using design expert software to optimize the base bleed formulations that can produce minimum amount of secondary smoke with the lowest flame temperature and higher impulse. The optimized base bleed propellant formulations, that have been found, were those of 10.27 and 7.02 % for both RDX/AP and Mg/AP ratios respectively. The experimental preparation and testing of the optimized two base bleed types showed lower values of secondary smoke by 16% and 55% for RDX/AP and Mg/AP ratios respectively when tested experimentally alongside the baseline base bleed reference composition.